2019
DOI: 10.22161/ijaers.6.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Technological productivity on control of Boophilus Microplus tick: A Patentometric Study

Abstract: The Boophilus Microplus tick is responsible for causing large losses in cattle, its control is based on the use of chemical products and this species has presented an increasingly resistance to the products used. The objective of this article is to evaluate the technological profile for the control of the Boophilus Microplus tick through a patentometric study. In order to identify the study, we used the patents of Espacenet and Derwent Innovations Index, where 514 patents were found and 245 were analyzed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…This study includes a survey of the technologies protected by patents of invention used in products and processes for obtaining green PEs (HDPE-high density polyethylene and PELBD-linear low density polyethylene) and green PP filed in the USPTO patent data base in a period of 18 years. In this work, through the related patentometry [15] it was evaluated how the technologies for the production and use of polyethylenes (PEs) and green polypropylenes evolved from 1999 to 2017. The USPTO was chosen because it has a wider scope, when compared to the European patent office.…”
Section: Introductionmentioning
confidence: 99%
“…This study includes a survey of the technologies protected by patents of invention used in products and processes for obtaining green PEs (HDPE-high density polyethylene and PELBD-linear low density polyethylene) and green PP filed in the USPTO patent data base in a period of 18 years. In this work, through the related patentometry [15] it was evaluated how the technologies for the production and use of polyethylenes (PEs) and green polypropylenes evolved from 1999 to 2017. The USPTO was chosen because it has a wider scope, when compared to the European patent office.…”
Section: Introductionmentioning
confidence: 99%
“…Herrero-Solana and Jürgens (2016) further studied collaboration among countries, identified top patenting institutions, top patenting regions. De Oliveira et al (2019) tried to assess technological productivity of the technologies developed to control Boophilus Microplus tick which is a parasitic disease among cattle and causes the death of a number of cattle every year. The authors found that technological publications like patents can be important markers of production activity and development of the field of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…This study includes a survey of the technologies protected by patents of invention used in products and processes for obtaining green PEs (HDPEhigh density polyethylene and PELBDlinear low density polyethylene) and green PP filed in the USPTO patent database in a period of 18 years. In this work, through the related patentometry [15] (OLIVEIRA, 2019) it was evaluated how the technologies for the production and use of polyethylenes (PEs) and green polypropylenes evolved from 1999 to 2017. The USPTO was chosen because it has a wider scope, when compared to the European patent office.…”
Section: Introductionmentioning
confidence: 99%